Genghis Khan's death (AD 1227): An unsolvable riddle or simply a pandemic disease?. (March 2021) - You, Wenpeng; Galassi, Francesco M.; Varotto, Elena; Henneberg, Maciej
Highlights: Based on historical sources, the cause of Genghis Khan's death may have been plague. Other etiologies suggested in the past appear to be later inventions made up by historians. Pandemic diseases do play a major historical role when they affect leaders. Abstract: The article examines Genghis Khan's death from the historico-medical perspective. Although several etiologies have been proposed over the years, most of these at a closer look appear to be later inventions by historians. A reassessment of the available evidence suggests instead bubonic plague as the most likely clinical scenario. Genghis Khan's death is also a reflection on the impact of pandemic diseases on leadership in ancient times as well as nowadays.